The Influence of Motivation, Discipline and Work Enviroment on Employee Performance in the Directorate of Planning, Organization and General Affairs our Hope Heart and Blood Vessel Hospital - Rahayu, Yuni Mardi; Pujiati, Herni (Dinasti Publisher, 2025)
Globalization in the world of the health industry continues to develop every time and every year, this causes competition in the business world, especially in the health service sector to increase. Then, with the implementation of the MEA (Asean Economic Community) agreement, the impact of which will lead to competition in the economy in the ASEAN region, the quality of business products and human resources will be more required to be competent. On this basis, the authors conducted a study entitled